Factors associated to sleep quality on informal drivers of interprovincial buses at high geographic altitude in Peru - Huamán Olarte, Ramón Julio (2020)
Objective. To determine the factors associated with sleep quality (SQ) in informal interprovincial road bus drivers of Lima-Huancayo central highway during January to March 2018. Methods. Cross-sectional study. Occupational and sociodemographic data were obtained. Pittsburgh Sleep Quality Index (PSQI) was applied. Prevalence and factors associated with SQ were obtained. Results. 162 drivers took part in the study. The average age was 42 ± 10,2 years, 55,6% had a technical instruction education level, 42% were married and 55,6% had between two and three children, 54,9% were overweight and 32,1% had obesity. The average time of work experience as a driver was 17 ± 6,8 years; the average PSQI was 8,1 ± 3. The 89,6 % showed a high frequency of disturbed SQ with variable degrees. Age (p = 0,03) is the factor associated with SQ. Conclusion. There is a high prevalence of disturbed SQ among informal drivers. Age constituted the main factor associated with SQ.